(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: This study evaluated the effects of Moringa oleifera leaf meal incorporation in local Guinea fowl breeders’ diet on the hatching rate, quality, and serum parameters of Keet in Togo. Materials and Methods: For this study, 512 breeder Guinea fowls (128 males and 384 females) were assigned randomly to four dietary groups (with four replicates each), named DT0, DT1, DT2, and DT3, containing, respectively, 0%, 0.5%, 1%, and 1.5% of M. oleifera leaf powder in diets. Guinea fowls are raised in confinement. Four incubations (I38, I42, I46, and I50) of 560 eggs were carried out each (Incubated at 37.7°C, with a relative humidity of 55%, the eggs were turned once per hour at a 90° angle until 23 days before transferred to hatching baskets for 3–4 days). These eggs were collected from 384 local Guinea fowls at 38, 42, 46, and 50 weeks of age. Egg weight loss, the duration of hatching events, fertility, hatchability, embryo mortality, and serum parameters of keets at hatch were evaluated. Results: The duration of the hatching events in the DT0 and DT1 treatments was higher than that of the DT2 and DT3 groups. The fertility rate (%) in DT2 and DT3 (76.43 ± 3.8 and 76.15 ± 4.5, respectively) was higher than that of DT0 and DT1 (73.3 ± 6.6 and 74.2 ± 4.7, respectively). Hatchability (%) was lower in DT0 (81.5 ± 3.3) compared to DT1, DT2, and DT3 (87.54 ± 5.5, 87.03 ± 3.2, and 88.25 ± 4.1, respectively). Embryo mortality rate (%) reduced in DT1, DT2, and DT3 (9.92 ± 0.24; 11.08 ± 0.34; and 11.12 ± 0.71, respectively) compared to DT0 (12.84 ± 1.59). The total proteins and albumin levels were higher in DT1, DT2, and DT3 compared to DT0. Alanine aminotransferase, aspartate aminotransferase, urea, uric acid, creatinine, high-density lipoproteins-cholesterol, and triglycerides levels for all treatments were not significantly different. Total cholesterol decreases in DT1, DT2, and DT3 compared to DT0. Conclusion: In conclusion, M. oleifera leaf meal incorporated into local Guinea fowl breeders’ diets at 0.5%, 1%, and 1.5% improves keets production. However, according to the results on egg production performance of Guinea fowl breeders obtained in our previous study, the best performance was obtained with dietary inclusion of 0.5% and 1% M. oleifera leaves powder. J. Adv. Vet. Anim. Res., 12(4): 1201–1210, December 2025 http://doi.org/10.5455/javar.2025.l980